Continuing care following residential alcohol and other drug treatment: Continuing care worker perceptions. (16th June 2021) - Ingram, Isabella; Kelly, Peter J.; Carradus, Lenna J.; Deane, Frank P.; Baker, Amanda L.; Byrne, Gerard; McKay, James R.; Osborne, Briony; Meyer, Johanna M.; Nunes, Jason L.; Robinson, Laura D.; Lunn, Joanne
Abstract: Introduction: Little is known about the experiences of continuing care workers (CCW) in the implementation of continuing care programs. The current study sought to understand CCWs and supervisor perceptions of the successes and challenges of implementing a telephone‐based continuing care intervention following residential alcohol and other drug treatment services. It also aimed to provide recommendations for treatment providers wishing to integrate continuing care into their treatment model, including the resources, training and supervision needs of CCWs. Methods: The participants were eight CCWs and two independent supervisors who completed semi‐structured interviews. Interview coding and analysis was guided by Iterative Categorisation procedures and an implementation framework. The Consolidated Framework for Implementation Research was used. Results: Telephone delivery was advantageous, but even more enhanced, when there was a face‐to‐face session first to build rapport. Other key successes included CCWs who were confident and competent, as well as a match between the organisation's values and the philosophy of the continuing care program. Key challenges faced by CCWs related to a perceived lack of support from managers, difficulties accessing quiet office spaces and participant disengagement. Discussion and Conclusions: Interviews revealed several factors that may influence successful delivery of continuing care as part of alcohol and other drug treatment. These included features of the intervention (e.g. telephone delivery, evidence‐based content), characteristics of the individual CCWs (e.g. flexibility in delivery of the intervention while maintaining fidelity), organisational culture (e.g. alignment of organisational values with continuing care) and resources (e.g. office space, flexible work schedules).